2007
DOI: 10.1007/s00467-007-0489-z
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular eNOS gene expression during postnatal maturation and AT1 receptor inhibition

Abstract: Glomerular maturation increases from immature superficial to advanced juxtamedullary nephrons, while nephrogenesis continues postnatally in porcine kidneys. Endothelial NOS, eNOS, shows significant postnatal renal developmental regulation, perhaps mediated by Angiotensin II (AII). The objective was to compare eNOS mRNA gene expression between superficial and juxtamedullary glomeruli obtained from piglets and adult pigs utilizing laser capture microdissection during basal conditions and, to determine the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Solhaug et al demonstrated pre-perfusion of an AT1 receptor inhibitor prior to NOS inhibition with L-NAME renal perfusion blunted the effects of L-NAME in the newborn, but not the adult, kidney (11). Ratliff et al demonstrated AT1 receptor inhibition in the newborn piglet attenuated glomerular eNOS expression (27). However, information on NOS regulation is much more available in the adult.…”
Section: Discussionmentioning
confidence: 99%
“…Solhaug et al demonstrated pre-perfusion of an AT1 receptor inhibitor prior to NOS inhibition with L-NAME renal perfusion blunted the effects of L-NAME in the newborn, but not the adult, kidney (11). Ratliff et al demonstrated AT1 receptor inhibition in the newborn piglet attenuated glomerular eNOS expression (27). However, information on NOS regulation is much more available in the adult.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate maturation of the other constituent cellular elements of the glomerulus has been shown to rely upon the effect of inductive signals such as platelet-derived and vascular endothelial-derived growth factors (PDGF and VEGF) derived from podocytes [27]. An inability of Ros to correct deficits in these pathways could also have a role to play in the incomplete protection of glomerular development during neonatal UUO.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, studies in animal models with ongoing postnatal nephrogenesis have shown that after birth there initially remains a low blood flow to the outer renal cortex which is likely a protective mechanism to protect developing, immature glomeruli in this region of the kidney [72]. It is unknown, however, whether this protective pattern of blood distribution is also present in the kidney of the preterm human neonate, which is especially important given that these kidneys are structurally very immature and nephrogenesis is still ongoing in the outer renal cortex after birth.…”
Section: Renal Blood Flow Increases At Birthmentioning
confidence: 99%